Small-Angle X-ray Scattering Study of the Effect of pH and Saltson 11S Soy Glycinin in the Freeze-Dried Powder andSolution States - Sokolova, A.; Kealley, Cat; Hanley, T.; Rekas, A.; Gilbert, E. (American Chemical Society, 2010)
The nanostructures from powders of native protein, glycinin, and corresponding solutions from whichthe powders have been formed, have been studied as a function of pH and 1 M salts using smallangleX-ray scattering. All powders showed Porod scattering with the exception of that preparedfrom the solution close to pI which displayed fractal behavior. Well-defined Bragg peaks in thepowder scattering at pH 5, pH 7, and 1 M NaCl indicate the presence of long-range order. Thescattering from solutions at pH 7, pH 9, and 1 M NaCl can be described well on the basis of particlesderived from the known atomic structures of homohexameric glycinin. Extreme acidic (pH 2) andbasic (pH 11) environments lead to the partial denaturation of glycinin. Decreasing the pH to 2initiates dissociation of the hexameric structure, while increasing the pH to 11, as well as thepresence of 1 M NaSCN, results in the formation of large unimodal particles. This is reflected by“featureless” SAXS patterns for both powders and solutions.